Vitality alliance: adventures in entrepreneurial consulting - Page, Robert A (The international journal of entrepreneurship and innovation, 2003)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/081-033-379-669-736 tex.type: [object Object]
Keywords: dept.mgt

Leadership as Place - Beatty, Ellen; Page, Robert (Leadership in Place: How Academic Professionals Can Find Their Leadership Voice, 2007)
Keywords: Administration; Universities and colleges; Faculty; Educational leadership; United States; Universities and colleges; dept.aa; dept.mgt; faculty_collection

Classical literature gives life to business paradox and systems integration - Page, Robert; Andoh, Samuel; Smith, Robert (Administrative Issues Journal Education Practice and Research, 2017)
1 citations (Crossref) [2023-10-31]
Keywords: dept.eco; dept.mgt

Hidden tradeoffs in sustainability initiatives - Page, Robert A; Robbins, Gregory (International Journal of Interdisciplinary Research, 2013)
Keywords: dept.mgt; peer-reviewed

The green MBA: a competing values matrix - Page, Robert A; Collins, Kirsten A (Competitiveness Review: An International Business Journal Incorporating Journal of Global Competitiveness, 2010)
Purpose – The purpose of this paper is to review and categorize the different strategies Master of Business Administration (MBA) programs have adopted towards incorporating environmental sustainability into business administration. Design/methodology/approach – Through extensive internet research looking at colleges and universities, data are collected from primary source web sites and administrative school contacts. There are 35 institutions whose MBA programs address sustainability in some way. Each of these institutions is then organized by location, tuition cost, enrollment, year founded, accreditation, and curriculum. Findings – Green educational strategies differentiate themselves by the size and maturity of the program. Larger, established institutions typically opt for the green major, or a dual degree, and tend to leave systematic integration of sustainability to the individual student. Newer and smaller entrants tend to either dabble in green with a few sustainability courses, or completely embrace and systemically integrate sustainability throughout the program. Research limitations/implications – The sample focuses on US institutions and treats sustainability as an externally validated curricular choice when it may merely be an educational fad. The sample excludes potential green MBA programs that lack a strong internet presence. Practical implications – Four archetypes are identified: dual degree, all-green, green major, and green coursework. Institutions can analyze their performances and see where they fall on the two major continua – integration and maturity/size. Originality/value – Green MBA programs are relatively new on the academic landscape, and this research paper is one of the first to systematically analyze and categorize them. © Emerald Group Publishing Limited.
4 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/062-866-418-386-446 tex.type: [object Object]
Keywords: Curricula; Economic sustainability; Education; Environmental studies; Master of business administration; dept.mgt

Aligning health care: quality as a learning system - Goralski, Margaret A; Page, Robert A (Estableciendo puentes en una economía global, Vol. 1, 2008 (Ponencias), ISBN 978-84-7356-556-1, pág. 36, 2008)
Citation Key Alias: lens.org/037-680-207-604-077
Keywords: dept.mgt; ⛔ No DOI found

The Risks and Rewards of Computing Everywhere for Small Business Entrepreneurs. - Bassett, Richard A.; Richardson, Anthony S.; Page, Robert A. (Issues in Information Systems, 2015)
Keywords: dept.bis; dept.mgt; peer-reviewed

Sustainability and stratified noncompliance in the pharmaceutical industry - Page, Robert A.; Cyr, Danielle M.; Richardson, Anthony S. (Journal of International Business Disciplines, 2015)
Keywords: dept.bis; dept.mgt; peer-reviewed

Start-up and hiring practices of immigrant entrepreneurs: An empirical study from an evolutionary psychological perspective - Yang, Chulguen; Colarelli, Stephen M; Han, Kyunghee; Page, Robert A (International Business Review, 2011)
Strong social ties embedded in ethnic communities of immigrant populations have been considered key assets for immigrant entrepreneurs. However, little research has been done on how biological kinship and the biological theories of altruism influence the behavior of ethnic entrepreneurs. In this study, we have applied a neo-Darwinian evolutionary theory of kinship to examine adaptive functions of kin and ethnic altruism in business start-up and hiring practices of Korean immigrant entrepreneurs in the United States. We confirmed that the patterns of help received by Korean entrepreneurs for business start-ups were congruent with an evolutionary perspective on altruism. However, the results for hiring patterns suggested that customer ethnicity trumped kin and co-ethic interests. We close by offering suggestions for future research. (C) 2011 Elsevier Ltd. All rights reserved.
23 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/092-753-567-946-985 tex.type: [object Object]
Keywords: Ethnic nepotism; Evolutionary psychology; Immigrant entrepreneurship; Inclusive fitness theory; Kin altruism; dept.mgt

40 years of academic public psychiatry - ethnicity, mental health care disparities and culturally competent care at the connecticut mental health center - Nazroo, James; Blue, Howard C.; Añez, Luis M.; Paris, Manuel; Hawkins, Dietra; Page, Robert A. (John Wiley & Sons, Ltd, 2007)
Keywords: dept.mgt

Ethnicity, mental health care disparities and culturally competent care at the connecticut mental health center - Nazroo, James; Blue, Howard C; Anez, Luis M; Paris, Manuel; Hawkins, Dietra; Page, Robert A (40 Years of Academic Public Psychiatry, 2007)
Keywords: Community-based prevention efforts; Deinstitutionalization impact; Housing and employment discrimination; Psychotic disorders and unrelenting affective disorders; Third psychiatric revolution; dept.mgt